PENGGUNAAN STRATEGI CREATIF PROBLEM SOLVING DALAM PEMBELAJARAN PUISI SISWA KELAS II MADRASAH ALIYAH GOTALAMO MOROTAI SELATAN - M. Rais Salim (Universitas Khairun, 2017)
Statement of the problems are: (1) How to learn Poetry at the second Class Students of Madrasah Aliyah Man Model through the use of strategy creative problem solving ? (2) how is the result of lerning poetry at Madrasah Aliyah Gotalamo Morotai Selatan Through the use of strategy creative problem solving ? this research aimed to (1) to know the learning poetry through the use of strategy creatife problem solving at Madrasah Aliyah Gotalamo Morotai Selatan. (2) to know wether the result of learning poetry through through the use of strategy creative problem solving at Madrasah Aliyah Gotalamo Morotai Selatan.This research is locaed in Madrasah Aliyah Gotalamo Morotai Selatan which is in Desa Darame. Analyzing data by using descriptive parentage. The subject of this research is the Second class student of Man Model constist of 45% students. The Sample was taken randomly, data collecting technique include of (1) observation (2) angket.The result shows that the students who are interesting in the use of strategy creative problem solving in learning poetry, it can be seen from the result of data analysis. After data collecting, then analyze through the formula of the presentage, the result of students scores are 65% it can be concluded that the students are interesting in learning poetry through creative problem solving at the second class students of Aliyah Gotalamo Morotai Selatan. Key Word: Creatif Problem Solving, poem